2008
DOI: 10.1002/bit.21820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adhesion to activated carbon particles on the viability of waterborne pathogenic bacteria under flow

Abstract: In rural areas around the world, people often rely on water filtration plants using activated carbon particles for safe water supply. Depending on the carbon surface, adhering microorganisms die or grow to form a biofilm. Assays to assess the efficacy of activated carbons in bacterial removal do not allow direct observation of bacterial adhesion and the determination of viability. Here we propose to use a parallel plate flow chamber with carbon particles attached to the bottom plate to study bacterial adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Terada et al investigated the effect of material surface charge property on E. coli adhesion and survival, and found that electrostatic attraction forces induced more bacterial retention and lower viability. Other studies have also reported that positively charged biomaterial surfaces exert an antimicrobial effect on adhering bacteria, while negatively charged surfaces have no significant effects on bacterial viability or metabolic activity. In this study, positively charged goethite can attract bacteria through long-range electrostatic forces, while negatively charged montmorillonite and kaolinite repulse bacteria (Figure S1). Therefore, the stronger and closer association between bacteria and goethite is responsible for lower bacterial viability as compared to cells bound to montmorillonite and kaolinite.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…Terada et al investigated the effect of material surface charge property on E. coli adhesion and survival, and found that electrostatic attraction forces induced more bacterial retention and lower viability. Other studies have also reported that positively charged biomaterial surfaces exert an antimicrobial effect on adhering bacteria, while negatively charged surfaces have no significant effects on bacterial viability or metabolic activity. In this study, positively charged goethite can attract bacteria through long-range electrostatic forces, while negatively charged montmorillonite and kaolinite repulse bacteria (Figure S1). Therefore, the stronger and closer association between bacteria and goethite is responsible for lower bacterial viability as compared to cells bound to montmorillonite and kaolinite.…”
Section: Resultsmentioning
confidence: 49%
“…A few studies have examined the viability of cells on different biomaterial surfaces in a parallel plate flow chamber using the Live/Dead viability kit. For example, van der Mei et al reported that polydiallyldimethylammonium chloride (p-DADMAC) coatings on glass enhanced adhesion and reduced the viability of selected bacteria by the positively charged ammonium groups. Compared to basic wood-based carbon and coconut-based carbon, the number of Raoultella terrigena and E. coli adhesion to the acidic wood-based carbon was the highest and caused the greatest loss of viability . Recently, Asadishad et al demonstrated Live/Dead BacLight staining technique was sensitive enough to distinguish between the loss of viability kinetics of different bacteria attached to various surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egestion rates are proportional to ingestion rates and thus can be used to judge food uptake and to explain possible effects observed during lipid content determinations; and (v) bacterial community structure (analyzed by terminal restriction fragment length polymorphism, T-RFLP). AC is capable of adhering bacteria , possibly leading not only to an initially reduced viability but also to colonization and biofilm formation . Depending on changes in substrate availability or the percentage of surface-attached bacteria, changes in the community composition might thus occur.…”
Section: Experimental Designmentioning
confidence: 99%
“…Another strategy for antibacterial functionalization is to create surface charges. Van der Mei et al have reported that a positively charged carbon surface can reduce the viability of bacteria 16 . Positive or negative surface charges have also been found to promote the antibacterial efficiency of chitosan and inhibit adherence of Gram-negative bacteria on polymeric materials 17 20 .…”
Section: Introductionmentioning
confidence: 99%